Periprocedural complications of cardiac implantable electronic device implantation in very elderly patients with cognitive impairment: A prospective study. Issue 46 (19th November 2021) - Guan, Fu; Peng, Jianjun; Hou, Shu; Ren, Lihui; Yue, Yunan; Li, Guangping
Abstract : Abstract: Very elderly people (over 80 years) with cardiac implantable electronic devices (CIEDs) indications often have a higher prevalence of aging comorbidity, among which cognitive impairment is not uncommon. This study aimed to investigate periprocedural complications of CIED implantation among very elderly patients with and without cognitive impairment. One hundred eighty patients ≥80 years of age indicated for CIED implantation were included in our study. During hospitalization, the cognitive evaluation was performed according to the Diagnostic and Statistical Manual of Mental Disorders (fifth edition). According to the cognitive test results, patients were divided into 2 groups (90 patients with normal cognitive function and 90 patients with cognitive impairment). Meanwhile, their physical parameters and laboratory measurements were completed. The procedural data and periprocedural complications were collected from both groups. The association between cognitive impairment and periprocedural complications was analyzed using univariate and multiple logistic regression analyses. During a one-month follow-up, the most frequent periprocedural complications in very elderly patients were pocket hematoma and thrombosis events. Cognitively impaired patients had a higher incidence of complications than normal cognitive patients. Multivariate regression analysis showed that cognitive impairment was positively correlated with periprocedural complications in very elderly patients. Cognitive impairment is associated with increased periprocedural complications of CIED implantation in very elderly patients.